Preparation method of liquid rubber, liquid rubber and rubber composite material
By conducting the polymerization of liquid rubber under anhydrous and oxygen-free conditions, a complex of hydrocarbon aluminum and organic boron salt and conjugated diene is used to form a high cis-1,4-structural unit selectivity and a low molecular weight distribution. The liquid rubber solves the problems of high catalyst dosage and wide molecular weight distribution, and significantly improves material performance and production efficiency.
Patent Information
- Application Number
- CN202411235730.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-04
- Publication Date
- 2024-12-13
AI Technical Summary
In the existing liquid rubber preparation methods, the high amount of catalyst, wide molecular weight distribution, and low selectivity of cis-1,4-structural unit, resulting in poor material performance and high solvent contamination and cost.
Under anhydrous and oxygen-free conditions, the complex of the structure of formula I, hydrocarbon aluminum and organic boron salt are mixed with C4-C20 conjugated diene for polymerization to form a high cis-1,4-structure unit selectivity , liquid rubber with a narrow molecular weight distribution can reduce the amount of catalyst through the active chain transfer system.
It has achieved low catalyst usage, narrow molecular weight distribution of liquid rubber, and high selectivity of cis-1,4-structure units, which significantly improves the tensile strength and tear strength of rubber composite materials and reduces production costs.
Smart Images

Figure BDA0005027679470000031 
Figure BDA0005027679470000081 
Figure BDA0005027679470000082
Abstract
Description
Technical Field
[0001] The present invention relates to the field of rubber technology, and in particular to a method for preparing liquid rubber, liquid rubber and a rubber composite material. Background Art
[0002] Petroleum-based oils are commonly used petroleum plasticizers with phthalate or aromatic structures, small molecular weight but certain volatility. Therefore, they will evaporate during mixing with rubber or be discharged from rubber products through leakage or frost spraying during long-term storage, which significantly shortens the service life of rubber products. Especially in tire rubber, as the tire continues to wear, petroleum-based oils are discharged together with the rubber, which seriously affects the use of the tire and has an adverse impact on the environment.
[0003] In recent years, liquid rubber has received extensive attention from researchers as a rubber additive. Liquid rubber generally has a relative molecular mass of 500-10000. It is a viscous polymer with fluidity at room temperature. When subjected to external force, it not only exhibits viscosity, but also elasticity and plasticity. The molecular chain structure of liquid rubber is similar to that of general-purpose butadiene rubber, and the two have good compatibility. Therefore, liquid rubber can replace low-molecular petroleum-based oil as a rubber additive and participate in the cross-linking reaction during the rubber vulcanization process. This reactive additive exists stably in rubber products, will not migrate, volatilize, or be extracted with the solvent, so that the prepared vulcanized rubber will not shrink, pollute, deform, etc., and thus has good physical and mechanical properties and chemical stability, and can be better applied to fields with demanding material properties such as aerospace, high-speed rail trains and high-performance automobiles.
[0004] The higher the cis-1,4-content in butadiene rubber, the lower its glass transition temperature and the better its low temperature resistance. In the prior art, diene liquid rubber is mainly prepared by free radical and anionic polymerization, but the stereoregularity of the polymer cannot be effectively controlled. The liquid diene rubber produced by free radical polymerization is basically an irregular structure with an extremely low cis content. The anionic polymerization method can prepare liquid rubber with a medium cis content. Its initiator generally uses an organic metal compound. After the reaction is completed, a terminator needs to be added, and there will be initiator residues in the polymer. When terminated with water or alcohol, water or alcohol will react with the organic lithium compound to form lithium hydroxide or alkoxy lithium, which will make the liquid rubber yellow. In addition, lithium hydroxide and alkoxy lithium are highly alkaline and will react with antioxidants, affecting the anti-aging performance of the antioxidant, resulting in changes in the performance of the liquid rubber during heating, storage and use, especially yellowing of the appearance, which greatly limits the scope of use of the product.
[0005] Rare earth metal catalysts have excellent performance in the high-selectivity polymerization of conjugated dienes, and the cis-1,4-selectivity of the polymer is above 80%. Patents US2008182954-A1 and JP2008163338-A report a method for preparing liquid polybutadiene using a rare earth system, wherein the content of cis-1,4-structural units of the liquid butadiene obtained by the method is ≥95%, but the method requires methylaluminoxane (MAO) as a co-catalyst during the catalyst preparation process, and toluene is required as a solvent, which not only increases the catalyst preparation cost, but also pollutes the environment and is difficult to recycle.
[0006] Patent CN101735364A discloses a method for preparing liquid polybutadiene rubber using a binary system composed of a rare earth organic sulfonic acid compound and an alkyl aluminum. The method uses hexane as a reaction solvent, which reduces the harm of toxic solvents to humans and the environment and reduces the production cost caused by solvent recovery. However, the catalyst activity of the method is low, the molecular weight distribution of the obtained liquid polybutadiene is relatively wide (4 to 6), and the cis content of the liquid rubber is not reported.
[0007] Patent CN102887966A discloses the application of a three-component rare earth catalyst system consisting of an alkoxy rare earth compound, a hydrogenated alkyl aluminum compound, and a chloride in the catalytic synthesis of liquid conjugated diene rubber. The cis-1,4-structural unit content of the obtained liquid butadiene rubber is between 95% and 98%; the cis-1,4-structural unit content of the obtained liquid isoprene rubber is between 85% and 98%. However, the presence of 3,4-structural units in the liquid isoprene rubber obtained in this patent will reduce the tensile properties of the rubber. In addition, the molar ratio of conjugated diene to rare earth catalyst in this patent is (100 to 1000): 1, and the amount of catalyst used is large. When producing a large amount of liquid rubber, the cost is high, which is not conducive to industrial production.
[0008] Therefore, researching and developing a new method for preparing liquid rubber is of great significance for the application of liquid rubber. Summary of the invention
[0009] In view of this, the technical problem to be solved by the present invention is to provide a method for preparing liquid rubber, liquid rubber and rubber composite material. The method uses a low amount of catalyst, and the prepared liquid rubber has the advantages of high selectivity of cis-1,4-structural units, low molecular weight and narrow molecular weight distribution.
[0010] The present invention provides a method for preparing liquid rubber, comprising the following steps:
[0011] Under anhydrous and oxygen-free conditions, the complex of formula I, alkyl aluminum hydride, organic boron salt and C4-C 20 The conjugated dienes are mixed and polymerized to obtain liquid rubber;
[0012]
[0013] Among them, the complex of formula I and C4-C 20 The molar ratio of the conjugated diene is 1:(50,000-300,000); more preferably 1:(50,000-250,000); further preferably 1:50,000 or 1:100,000 or 1:200,000 or 1:225,000 or 1:180,000.
[0014] The molar ratio of alkylaluminum hydride to the complex of formula I is (1000-10000):1; more preferably 1000:1 or 4000:1 or 5000:1 or 6000:1 or 9000:1.
[0015] Preferably, the molar ratio of the organic boron salt to the complex of formula I is (0.5-10):1; more preferably (1-3):1; further preferably 1:1.
[0016] Preferably, the alkylaluminum hydride is selected from one or more of dimethylaluminum hydride, diethylaluminum hydride, di-n-propylaluminum hydride, di-n-butylaluminum hydride, diisopropylaluminum hydride, diisobutylaluminum hydride, dipentylaluminum hydride, dihexylaluminum hydride, dicyclohexylaluminum hydride and dioctylaluminum hydride; more preferably, diisopropylaluminum hydride or diisobutylaluminum hydride.
[0017] Preferably, the C4-C 20 The conjugated diene is selected from one or more of 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 2-ethyl-1,3-butadiene, 2-phenyl-1,3-butadiene, 1,3-hexadiene, 4-methyl-1,3-pentadiene, 1,3-pentadiene, 3-methyl-1,3-pentadiene, 2,4-dimethyl-1,3-pentadiene or 3-ethyl-1,3-pentadiene; more preferably, one or more of 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene and 2-ethyl-1,3-butadiene.
[0018] In the present invention, the organoboron compound is an ionic compound formed by an organoboron anion and a cation;
[0019] The organic boron anion is selected from tetraphenylborate ([BPh4]-), tetrakis(monofluorophenyl)borate, tetrakis(difluorophenyl)borate, tetrakis(trifluorophenyl)borate, tetrakis(tetrafluorophenyl)borate, tetrakis(pentafluorophenyl)borate ([B(C6F5)4]-), tetrakis(tetrafluoromethylphenyl)borate, tetrakis(tolyl)borate, tetrakis(xylyl)borate, (triphenyl, pentafluorophenyl)borate, [tris(pentafluorophenyl), phenyl]borate or undecanoic acid-7,8-dicarbon undecanoate;
[0020] The cation is selected from carbonium cation, oxonium cation, ammonium cation, phosphonium cation, cycloheptatrienyl cation or ferrocenium cation containing transition metal;
[0021] The carbonium cation includes a trisubstituted carbonium cation such as a triphenylcarbonium cation ([Ph3C] + ) and a tri(substituted phenyl)carbonium cation, such as a tri(methylphenyl)carbonium cation, and the like;
[0022] The ammonium cations include trialkylammonium cations, dialkylammonium cations and N,N-dialkylanilinium cations. The trialkylammonium cations include trimethylammonium cations, triethylammonium cations ([NEt3H] + ), tripropylammonium cation and tributylammonium cation, etc.; the dialkylammonium cations such as diisopropylammonium cation and dicyclohexylammonium cation; the N,N-dialkylanilinium cations such as N,N-dimethylanilinium cation ([PhNMe2H] + ), N,N-diethylanilinium cation and N,N-2,4,6-pentamethylanilinium cation, etc.;
[0023] The phosphonium cation includes a triarylphosphonium cation such as a triphenylphosphonium cation, a tri(tolyl)phosphonium cation, or a tri(xylyl)phosphonium cation.
[0024] Preferably, the organic boron salt is selected from one or more of triphenylcarbonium tetrakis(pentafluorophenyl)borate [Ph3C][B(C6F5)4], dimethylanilinium N,N-tetraphenylborate [PhNMe2H][BPh4], triethylammonium tetraphenylborate [NEt3H][BPh4] or N,N-dimethylphenyl tetrakis(pentafluorophenyl)borate [PhNMe2H][B(C6F5)4].
[0025] More preferably, the alkylaluminum hydride is selected from diisobutylaluminum hydride;
[0026] More preferably, the C4-C 20 The conjugated diene is selected from 1,3-butadiene (BD) and / or isoprene (IP).
[0027] The polymerization reaction of the present invention includes homopolymerization and copolymerization;
[0028] When selected from BD or IP, the polymerization reaction is a homopolymerization reaction, and when selected from BD and IP, the polymerization reaction is a copolymerization reaction.
[0029] More preferably, the organic boron salt is selected from triphenylcarbonium tetrakis(pentafluorophenyl)borate [Ph3C][B(C6F5)4].
[0030] The present invention further preferably comprises: 20 When the conjugated diene is selected from 1,3-butadiene and isoprene, the molar ratio of 1,3-butadiene to isoprene is (1-9):1; more preferably 1:1 or 2.3:1 or 4:1 or 9:1.
[0031] In some specific embodiments of the present invention, when the C4-C 20 When the conjugated diene is selected from 1,3-butadiene, a liquid butadiene rubber is prepared; the number average molecular weight of the liquid butadiene rubber is Mn=(4.25-8.52)×10 3 , M n / M w =1.76-1.93, and the content of cis-1,4-structural units is 99%-99.3%.
[0032] In some specific embodiments of the present invention, when the C4-C 20 When the conjugated diene is selected from isoprene, a liquid isoprene rubber is prepared; the number average molecular weight of the liquid isoprene rubber is Mn=(1.65-13.46)×10 3 , M n / M w =1.81-1.98, and the content of cis-1,4-structural unit is 99%-99.3%.
[0033] In some specific embodiments of the present invention, when the C4-C 20 When the conjugated diene is selected from 1,3-butadiene and isoprene, a liquid butadiene / isoprene copolymer rubber is prepared, which is also called liquid butadiene-pentadiene rubber; the number average molecular weight of the liquid butadiene-pentadiene rubber is Mn=3.56-12.1, and M n / M w =1.66-1.91, and the content of cis-1,4-structural units is 99%-99.3%.
[0034] The temperature of the polymerization reaction of the present invention is preferably 25-100°C; more preferably 25-40°C; further preferably 40°C.
[0035] The polymerization reaction time is preferably 2-24 hours.
[0036] The present invention has no particular limitation on the container for the polymerization reaction, and the polymerization reaction can be carried out in a batch reactor or a continuous polymerization reactor.
[0037] The present invention has no particular limitation on the solvent for the polymerization reaction.
[0038] The solvent for the polymerization reaction is preferably one or more of aliphatic saturated hydrocarbons, aromatic hydrocarbons, aromatic halides and cycloalkanes; more preferably one or more of n-hexane, cyclohexane, benzene, toluene, xylene, chlorobenzene, dichlorobenzene and bromobenzene; in some specific embodiments of the present invention, n-hexane is preferred.
[0039] The preparation method of the present invention forms a better active chain transfer system by using the complex of formula I structure as a catalyst and a high proportion of alkyl aluminum hydride, so that the amount of catalyst used in the preparation method is low, and the prepared liquid rubber has the advantages of high selectivity of cis-1,4-structural units, low molecular weight and narrow molecular weight distribution, which cannot be achieved by other chain transfer agents.
[0040] The present invention also provides a liquid rubber prepared by the above-mentioned preparation method.
[0041] Preferably, the content of cis-1,4-structural units in the conjugated diene units of the liquid rubber is greater than 99%;
[0042] Preferably, the number average molecular weight of the liquid rubber is 1000-15000; more preferably 1650-13460.
[0043] Preferably, the molecular weight distribution of the liquid rubber is 1-3; more preferably 1-2.
[0044] The present invention also provides a rubber composite material, the raw material of which includes the above-mentioned liquid rubber.
[0045] The raw materials of the above rubber composite materials also include diene elastomers, fillers, vulcanizers, accelerators, processing oils, fatty acids, waxes, resins and antioxidants.
[0046] The filler includes but is not limited to carbon black and white carbon black.
[0047] The diene-based elastomer includes, but is not limited to, natural rubber elastomer, polybutadiene elastomer, styrene-butadiene rubber elastomer, isoprene rubber elastomer, and the like.
[0048] The vulcanizing agent includes but is not limited to sulfur.
[0049] Preferably, the raw materials of the rubber composite material are butadiene rubber BR9000, isoprene rubber IR2200, carbon black N330, zinc oxide, stearic acid, antioxidant 4020, antioxidant RD, and sulfur.
[0050] In the above-mentioned rubber composite material, the liquid rubber has a plasticizing effect, and the liquid rubber of the present invention participates in the cross-linking reaction during the vulcanization process of the rubber matrix (the rubber which is the main component of the rubber composite material), so that the liquid rubber has a lower degree of volatilization and migration during the vulcanization process of the rubber composite material, and will not be extracted with the solvent, so that the rubber composite material has good physical and mechanical properties and chemical stability.
[0051] Furthermore, due to the high content of cis-1,4-structural units in the conjugated diene units of the liquid rubber, a rubber composite material with significantly improved tensile strength and tear strength can be obtained by adding a low content of the liquid rubber.
[0052] It is further preferred that the rubber composite material can be used to prepare elastomer products.
[0053] The elastomeric products include but are not limited to tire components, seismic isolation rubber, belts (conveyor belts), rubber tracks, hoses, sealing rings, etc.
[0054] Compared with the prior art, the preparation method of the liquid rubber provided by the present invention comprises the following steps: under anhydrous and oxygen-free conditions, a complex of formula I, alkyl aluminum hydride, an organic boron salt and a C4-C 20 The conjugated diene is mixed and polymerized to obtain liquid rubber; wherein the complex of formula I and C4-C 20 The molar ratio of the conjugated diene is 1:(50000-300000); the molar ratio of the alkyl aluminum hydride and the complex of the formula I structure is (1000-10000):1. The method of the present invention uses the complex of the formula I structure as a catalyst, combined with the chain transfer effect of the alkyl aluminum hydride, to form an active chain transfer system, so that the catalyst dosage in the preparation method is low, and the prepared liquid rubber has the advantages of high cis-1,4-structural unit content, low molecular weight and narrow molecular weight distribution. The liquid rubber prepared by the method is used to prepare rubber composite materials, which can significantly improve the tensile strength and tear strength of the material and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0055] Figure 1 The liquid butadiene rubber prepared in Example 1 1 HNMR spectrum;
[0056] Figure 2 The liquid butadiene rubber prepared in Example 1 13 CNMR spectrum;
[0057] Figure 3 The liquid butadiene / isoprene copolymer rubber prepared in Example 7 1 HNMR spectrum;
[0058] Figure 4 The liquid butadiene / isoprene copolymer rubber prepared in Example 7 13 CNMR spectrum;
[0059] Figure 5 The liquid isoprene rubber prepared in Example 7 1 HNMR spectrum;
[0060] Figure 6 The liquid isoprene rubber prepared in Example 7 13 CNMR spectrum. DETAILED DESCRIPTION
[0061] In order to further illustrate the present invention, the preparation method of the liquid rubber, the liquid rubber and the rubber composite material provided by the present invention are described in detail below in conjunction with embodiments.
[0062] The source of the complex of the following formula I structure is not particularly limited and can be prepared by methods well known to those skilled in the art, such as by the method disclosed in Organometallics 2011, 30(4), 760-767.
[0063] The following examples and comparative examples were all carried out under anhydrous and oxygen-free conditions.
[0064] Example 1
[0065] In a glove box, the complex of formula I (4 μmol) and triphenylcarbonium tetrakis(pentafluorophenyl)borate [Ph3C][B(C6F5)4] (3.7 mg, 4 μmol) were dissolved in 2 mL of toluene and stirred for 30 minutes, and then HAl was added. i Bu2 (24 mL, 24 mmol, 1.0 mol / L n-hexane solution) was added to obtain a clear active chain transfer catalytic system.
[0066] 0.8 mol (0.5 mol / L) of 1,3-butadiene (BD) n-hexane solution was added to a 500 mL stainless steel reactor fully purged with nitrogen and stirred thoroughly to form a polymerization reaction system.
[0067] Afterwards, the catalyst system solution was taken out from the glove box and quickly added to the above polymerization reaction system at 40°C to initiate polymerization. After 4 hours of reaction, 100 mL of methanol-hydrochloric acid solution was immediately added to terminate the reaction. Then a large amount of ethanol was added to separate the copolymer, and the copolymer was vacuum dried at 40°C until the polymer weight did not change. The monomer conversion rate was 97%. The number average molecular weight of the obtained liquid rubber was Mn=8.38×10 3 , M n / M w =1.89, and the content of cis-1,4-structural units is 99.2%.
[0068]
[0069] Embodiment 2-4
[0070] According to the method described in Example 1, the raw material ratios and reaction conditions in Table 1 were used to prepare polybutadiene liquid rubbers with different molecular weights. Table 1 is a summary of the raw material ratios, reaction conditions and test results of Examples 2-4 of the present invention.
[0071] Table 1 Preparation of liquid butadiene rubber
[0072]
[0073] Note: BD in the table represents 1,3-butadiene, Cat. represents a tridentate carbazole chelated rare earth alkyl complex, and h represents hours. Except for the conditions in the table, the rest are the same as Example 1.
[0074] Example 5
[0075] In a glove box, the complex of formula I (4 μmol) and triphenylcarbonium tetrakis(pentafluorophenyl)borate [Ph3C][B(C6F5)4] (3.7 mg, 4 μmol) were dissolved in 2 mL of toluene and stirred for 30 minutes. i Bu2 (24 mL, 24 mmol, 1.0 mol / L n-hexane solution) was fully stirred to prepare an active chain transfer catalyst system.
[0076] Into a 500 mL stainless steel reactor fully purged with nitrogen, 0.72 mol (0.5 mol / L) of 1,3-butadiene (BD) n-hexane solution and 0.18 mol of isoprene (IP) were added to form a polymerization reaction system.
[0077] Afterwards, the catalyst solution was taken out of the glove box and quickly added to the above polymerization reaction system at 40°C to initiate polymerization. After 4 hours of reaction, 100 mL of methanol-hydrochloric acid solution was immediately added to terminate the reaction. Then a large amount of ethanol was added to separate the copolymer, and the copolymer was vacuum dried at 40°C until the polymer weight did not change. The monomer conversion rate was 96%. The number average molecular weight of the obtained liquid rubber was Mn=7.92×10 3 , M n / M w =1.81, and the content of cis-1,4-structural units is 99.3%.
[0078] Embodiment 6-8
[0079] According to the method described in Example 5, the raw material ratios and reaction conditions in Table 2 were used to prepare butylene-pentene liquid rubbers of different molecular weights. Table 2 is a summary of the raw material ratios, reaction conditions and test results of Examples 6 to 8 of the present invention.
[0080] Table 2 Preparation of butadiene / isoprene copolymer rubber
[0081]
[0082] Note: BD in the table stands for 1,3-butadiene, IP stands for isoprene; Cat. stands for a tridentate carbazole-chelated rare earth alkyl complex, h stands for hours, [IP] 0 Indicates the initial concentration of isoprene. Except for the conditions in the table, the rest are the same as those in Example 5.
[0083] Example 9
[0084] In a glove box, the complex of formula I (4 μmol) and triphenylcarbonium tetrakis(pentafluorophenyl)borate [Ph3C][B(C6F5)4] (3.7 mg, 4 μmol) were dissolved in 2 mL of toluene and stirred for 30 minutes. Then HAl i Bu2 (24 mL, 24 mmol, 1.0 mol / L n-hexane solution) was fully stirred to prepare an active chain transfer catalytic system.
[0085] 0.72 mol of isoprene (IP) and 300 mL of n-hexane were added to a 500 mL stainless steel reactor fully purged with nitrogen, and the mixture was fully stirred to form a polymerization reaction system.
[0086] Afterwards, the catalyst solution was taken out of the glove box and quickly added to the above polymerization reaction system at 40°C to initiate polymerization. After 4 hours of reaction, 100 mL of methanol-hydrochloric acid solution was immediately added to terminate the reaction. Then a large amount of ethanol was added to separate the copolymer, and the copolymer was vacuum dried at 40°C until the polymer weight did not change. The monomer conversion rate was 98%. The number average molecular weight of the obtained liquid rubber was Mn=8.59×10 3 , M n / M w =1.87, and the content of cis-1,4-structural units is 99.3%.
[0087] Examples 10-12
[0088] According to the method described in Example 9, the raw material ratios and reaction conditions in Table 3 were used to prepare isoprene liquid rubbers with different molecular weights. Table 3 is a summary of the raw material ratios, reaction conditions and test results of Examples 10-12 of the present invention.
[0089] Table 3 Preparation of liquid isoprene rubber
[0090]
[0091] Note: IP in the table represents isoprene, Cat. represents a tridentate carbazole chelated rare earth alkyl complex, and h represents hours. Except for the conditions in the table, the rest are the same as those in Example 9.
[0092] Comparative Example 1
[0093] According to the method described in Example 1, the difference is that the chain transfer agent HAliBu2 (diisobutylaluminum hydride) is replaced by AliEt3 (triethylaluminum), and the operation is as follows:
[0094] In a glove box, the complex of formula I (4 μmol) and triphenylcarbonium tetrakis(pentafluorophenyl)borate [Ph3C][B(C6F5)4] (3.7 mg, 4 μmol) were dissolved in 2 mL of toluene and stirred for 30 minutes. Al i Et3 (24 mL, 24 mmol, 1.0 mol / L n-hexane solution) was added to obtain the catalytic system.
[0095] 0.8 mol (0.5 mol / L) of 1,3-butadiene (BD) n-hexane solution was added to a 500 mL stainless steel reactor fully purged with nitrogen, and the mixture was fully stirred to form a polymerization reaction system.
[0096] Afterwards, the catalyst system solution was taken out from the glove box and quickly added to the above polymerization reaction system at 40°C to initiate polymerization. After 4 hours of reaction, 100 mL of methanol-hydrochloric acid solution was immediately added to terminate the reaction. Then a large amount of ethanol was added to separate the copolymer, and the copolymer was vacuum dried at 40°C until the polymer weight did not change. The monomer conversion rate was 97%. The number average molecular weight of the obtained liquid rubber was Mn = 9.64×10 5 , M n / M w =2.43, and the content of cis-1,4-structural unit is 99.0%.
[0097] Comparative Example 2
[0098] According to the method described in Example 5, the difference is that the chain transfer agent HAliBu2 (diisobutylaluminum hydride) is replaced by AliBu3, and the operation is as follows:
[0099] In a glove box, the complex of formula I (4 μmol) and triphenylcarbonium tetrakis(pentafluorophenyl)borate [Ph3C][B(C6F5)4] (3.7 mg, 4 μmol) were dissolved in 2 mL of toluene and mixed and stirred for 30 minutes. Then Al i Bu3 (1.2 mL, 1.2 mmol, 1.0 mol / L toluene solution) was used to prepare the catalyst solution.
[0100] Into a 500 mL stainless steel reactor fully purged with nitrogen, 0.72 mol (0.5 mol / L) of 1,3-butadiene (BD) n-hexane solution and 0.18 mol of isoprene (IP) were added and stirred sufficiently to form a polymerization reaction system.
[0101] Afterwards, the catalyst solution was taken out of the glove box and quickly added to the above polymerization reaction system at 40°C to initiate polymerization. After 4 hours of reaction, 100 mL of methanol-hydrochloric acid solution was immediately added to terminate the reaction. Then a large amount of ethanol was added to separate the copolymer, and the copolymer was vacuum dried at 40°C until the polymer weight did not change. The monomer conversion rate was 96%. The number average molecular weight of the obtained liquid rubber was Mn = 1.06×10 6 , M n / M w =2.33, and the content of cis-1,4-structural units is 99.3%.
[0102] Comparative Example 3
[0103] The method described in Example 9 was followed, except that the chain transfer agent HA1 i Bu2 (diisobutylaluminum hydride) is replaced by ZnEt2 (diethylzinc) as follows:
[0104] In a glove box, the complex of formula I (4 μmol) and triphenylcarbonium tetrakis(pentafluorophenyl)borate [Ph3C][B(C6F5)4] (3.7 mg, 4 μmol) were dissolved in 2 mL of toluene and mixed and stirred for 30 minutes. ZnEt2 (24 mL, 24 mmol, 1.0 mol / L n-hexane solution) was added to prepare a catalyst solution.
[0105] 0.72 mol of isoprene (IP) and 300 mL of n-hexane were added to a 500 mL stainless steel reactor fully purged with nitrogen and stirred thoroughly to form a polymerization reaction system.
[0106] Afterwards, the catalyst solution was taken out of the glove box and quickly added to the above polymerization reaction system at 40°C to initiate polymerization. After 4 hours of reaction, 100 mL of methanol-hydrochloric acid solution was immediately added to terminate the reaction. Then a large amount of ethanol was added to separate the copolymer, and the copolymer was vacuum dried at 40°C until the polymer weight did not change. The monomer conversion rate was 48%. The number average molecular weight of the obtained liquid rubber was Mn=8.59×10 5 , M n / M w =3.87, and the content of cis-1,4-structural units is 76.3%.
[0107] By comparing Examples 1-12 and Comparative Examples 1-3, it can be seen that the present invention uses HAliBu2 as a chain transfer agent, which has a molecular weight adjustment ability that other agents do not have, can achieve better active chain transfer polymerization ability, and better control molecular weight distribution.
[0108] Application Example 1
[0109] Application of Liquid Rubber in Rubber Mixing
[0110] (1) adding olefin rubber to an internal mixer, mixing at 60-80° C. for 60-150 seconds, then adding a reinforcing agent, zinc oxide, stearic acid, an antioxidant, and liquid rubber, mixing at 60-80° C. for 300-500 seconds, then adding sulfur and an accelerator and continuing to mix for 300-400 seconds to obtain a mixed rubber;
[0111] (2) The product obtained in step (1) is thinned on a two-roll mill at 40-80° C. for 15-30 times and left for 12-24 hours.
[0112] (3) vulcanizing and crosslinking the product obtained in step (2) at 120-190° C. to obtain the rubber composite material based on high-cis liquid rubber.
[0113] The present invention has no special restrictions on the cross-linking conditions, which can be selected according to the application. Preferably, the cross-linking is first carried out at 120-190° C. after a heating time of 3 min-800 min.
[0114] The liquid rubber prepared in Examples 3, 6 and 11 are used to form rubber compositions 1, 2 and 3, which are then prepared according to the above method to obtain vulcanized rubber, namely the rubber composite material based on high-cis liquid rubber.
[0115] The control group composite material was prepared and mixed using aromatic oil (TDAE) according to the above method.
[0116] The specific components and contents of the rubber compositions 1, 2, 3 and the control group are shown in Table 4, and the properties of the vulcanized rubber (rubber composite material) prepared from the rubber compositions 1, 2, 3 and the control group are shown in Table 5.
[0117] Table 4 Tread rubber composite material formula
[0118]
[0119] Table 5 Vulcanized rubber properties
[0120] Performance parameters Rubber composition 1 Rubber composition 2 Rubber composition 3 Control group Tensile strength(MMPa) 21.2 19.7 25.8 18.7 Elongation at break (%) 830 860 770 880 Tear strength(kN / mm) 42.7 36.2 91.2 35.5
[0121] The above results show that after adding the liquid rubber described in the present invention, the tensile strength and tear strength of the rubber composition material are significantly improved, indicating that the liquid rubber prepared by the present invention has broad application prospects in the fields of high-performance tires and the like.
[0122] The above embodiments are only used to help understand the method and core idea of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing liquid rubber, characterized in that: The following steps are involved: Under anhydrous and oxygen-free conditions, the complex of formula I, alkyl aluminum hydride, organic boron salt and C4-C 20 The conjugated dienes are mixed and polymerized to obtain liquid rubber; Among them, the complex of formula I and C4-C 20 The molar ratio of the conjugated diene is 1:(50000-300000); The molar ratio of alkylaluminum hydride to the complex of formula I is (1000-10000):
1.
2. The preparation method according to claim 1, characterized in that: The molar ratio of the organic boron salt to the complex of formula I is (0.5-10):
1.
3. The preparation method according to item 1, characterized in that: The alkylaluminum hydride is selected from one or more of dimethylaluminum hydride, diethylaluminum hydride, di-n-propylaluminum hydride, di-n-butylaluminum hydride, diisopropylaluminum hydride, diisobutylaluminum hydride, dipentylaluminum hydride, dihexylaluminum hydride, dicyclohexylaluminum hydride, and dioctylaluminum hydride.
4. The preparation method according to claim 1, characterized in that: The C4-C 20 The conjugated diene is selected from one or more of 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 2-ethyl-1,3-butadiene, 2-phenyl-1,3-butadiene, 1,3-hexadiene, 4-methyl-1,3-pentadiene, 1,3-pentadiene, 3-methyl-1,3-pentadiene, 2,4-dimethyl-1,3-pentadiene or 3-ethyl-1,3-pentadiene.
5. The preparation method according to claim 1, characterized in that: The organic boron salt is selected from one or more of triphenylcarbonium tetrakis(pentafluorophenyl)borate, N,N-dimethylphenyl tetrakisborate, triethylamine tetrakisborate or N,N-dimethylphenyl tetrakisborate.
6. The preparation method according to claim 1, characterized in that: The alkylaluminum hydride is selected from diisobutylaluminum hydride; The C4-C 20 The conjugated diene is selected from 1,3-butadiene and / or isoprene; The organic boron salt is selected from triphenylcarbonium tetrakis(pentafluorophenyl)borate.
7. The preparation method according to claim 6, characterized in that: The C4-C 20 When the conjugated diene is selected from 1,3-butadiene and isoprene, the molar ratio of 1,3-butadiene to isoprene is (1-9):
1.
8. A liquid rubber, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 7.
9. The liquid rubber according to claim 8, characterized in that The content of cis-1,4-structural units in the conjugated diene units of the liquid rubber is greater than 99%; The number average molecular weight of the liquid rubber is 1000-15000; The molecular weight distribution of the liquid rubber is 1-3.
10. A rubber composite material, characterized in that: The raw material comprises the liquid rubber as claimed in claim 8 or 9.
Citation Information
Patent Citations
Method for preparing liquid polybutadiene rubber by sulfoacid rare earth catalyst
CN101735364A
Rare earth catalysis system and application thereof in preparation of conjugated diene liquid rubber
CN102887966A
Method for manufacturing modified cis-1,4-polydiene having high cis-1,4-bond quantity and high functionality
JP2008163338A
Method for producing functionalized cis-1,4-polydienes having high cis-1,4-linkage content and high functionality
US20080182954A1
Polymerization catalyst for conjugated diene polymer, process for producing conjugated diene polymer with the same, rubber composition for tire, and rubber composition for golf ball
CN101052660A
